Relationship Between Motivational Factors and Teachers’ Performance on the Job in Ogba/ Egbema/ Ndoni Local Government Area, of Rivers State - Uche, Ahiauzu Levi; Fiberesima, Diepriye; Onwuchekwa , Christiana A. (Richtmann Publishing, 2011)
This study investigated the relationship between motivational factors and teacher’s performance on the job. A sampleof 150 teachers was randomly drawn from 10 secondary schools in Ogba Egbema Ndoni Local Government Area of RiversState. The study made use of correlational research design. The findings indicated that there is a significant relationshipbetween motivational factors and teacher’s’ performance and a significant relationship existing between teachers experience andtheir job performance. Some recommendations such as providing highly motivated, conscientious and efficient classroomteachers, encourage the spirit of enquiry and creativity in teachers, help teachers to fit into the social life of the community andsociety at large, enhance teachers commitment to the teaching profession etc, were also highlighted that have implications foreducational practice.